El espíritu del 12 de febrero y el fantasma de la crisis económica de 1974: un análisis a través del humor gráfico - Segado Boj, Francisco (Historia y Comunicación Social, 2007)
This paper researches into the cartoons published between February and October 1974 by the five most relevant Spanish newspapers in order to analyze the image projected by this medium of the economic crisis developed during this period.